Efficacy of Low-Dose rhGM-CSF Treatment in a Patient With Severe Congenital Neutropenia Due to CSF3R Deficiency: Case Report of a Novel Biallelic CSF3R Mutation and Literature Review - Zhou, Junli; Sun, Chengjun; Huang, Honglin; Zhu, Qiguo; Wen, Fengyun; Dong, Ying; Wang, Hongsheng (Frontiers in Pediatrics, 2021)
This study reports the clinical manifestations, genetics, and efficacy of treatment with the efficacy of recombinant human granulocyte macrophage colony-stimulating factor (rhGM-GSF) of a 2-year-old female patient with severe congenital neutropenia (SCN) type 7 (SCN7) caused by novel biallelic mutations in the colony-stimulating factor 3 receptor (CSF3R) gene. Genetic diagnosis of the patient was performed by whole-exome and Sanger sequencing. Expression of the CSF3R gene in the peripheral neutrophils of the patient was detected by real-time PCR and Western blotting. The patient presented with recurrent suppurative tonsillitis and decreased absolute neutrophil count <0.5 × 109/L. Novel heterozygous mutations were found to be inherited from each parent (maternal c.690delC [p.met231Cysfs*32] and paternal c.64+5G>A). The patient's neutrophils had lower CSF3R mRNA and protein levels than those of the parents. Low-dose rhGM-CSF (3 μg/kg/day once a week) prevented recurrent infection in the patient. These results demonstrate that the clinical manifestations of SCN7 with biallelic CSF3R mutations and downregulated CSF3R can be effectively treated with rhGM-CSF.